Karakter Wanita Qur’ani dalam Tafsir Kontemporer: Studi terhadap Penafsiran al-Harari, az-Zuhaili, dan Quraish Shihab - Marlina, Tuti; Nur Aisah Simamora (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2025)
This research examines the construction of Qur'anic women in contemporary tafsir through a thematic and comparative approach to tafsir by Amin al-Harari, Wahbah az-Zuhaili, and Quraish Shihab. The research focuses on four main female figures in the Qur'an: Maryam, Asiyah, Queen Balqis, and Prophet Moses' mother. The findings show that the three mufasirs, despite having different manhajs - creed-centric, academic-fiqh, and contextual-humanist - agree that the greatness of Qur'anic women is determined by the qualities of faith, firmness, tawakkal, intelligence, and moral courage, not by gender or social position. Az-Zuhaili emphasises the legitimacy of female leadership and divine justice, al-Harari emphasises submission and spiritual depth, while Quraish Shihab emphasises contextual relevance and the human dimension. The thematic synthesis reveals that the Qur'anic woman is not a static ideal, but a process of spiritual and moral transformation that is relevant to the challenges of Muslim women today, including leadership inequality, work-family pressures, and identity stigma. The study concludes that contemporary tafsir opens space for a more inclusive, just and applicable understanding of the role of women in Islam.